1966
DOI: 10.1021/jf60144a021
|View full text |Cite
|
Sign up to set email alerts
|

Browning in Freeze-Dried Fruits, Effect of Moisture Content of Freeze-Dried Peaches and Bananas on Changes during Storage Related to Oxidative and Carbonyl-Amine Browning

Abstract: In both freeze-dried peaches and bananas during long-term storage in air at 28°C , little change was observed at storage moisture levels below 10% in total phenolic substances, free amino nitrogen, reducing sugar, and sucrose content. In both freeze-dried peaches and bananas, peroxidase activity decreased rapidly at all moisture levels during storage at 28°C. In both freeze-dried peaches and bananas, polyphenol oxidase activity was most stable at the lowest moisture levels and became relatively unstable at 8% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

1966
1966
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
1
2
0
3
Order By: Relevance
“…Samples without in-package desiccation lost up to 75% ascorbic acid within the same period of time. Similar results were reported by Karel and Nickerson (1964) and Draudt and Huang (1966), whose results suggested that moisture content should be reduced to the lowest possible level for prevention of ascorbic acid losses. On the other hand, extremely low levels of moisture result in a reduced nutritional quality in products such as avocados, tomatoes and some vegetables.…”
Section: Nutritional Valuesupporting
confidence: 90%
“…Samples without in-package desiccation lost up to 75% ascorbic acid within the same period of time. Similar results were reported by Karel and Nickerson (1964) and Draudt and Huang (1966), whose results suggested that moisture content should be reduced to the lowest possible level for prevention of ascorbic acid losses. On the other hand, extremely low levels of moisture result in a reduced nutritional quality in products such as avocados, tomatoes and some vegetables.…”
Section: Nutritional Valuesupporting
confidence: 90%
“…In dried fruits, where the main reaction is between carbonyl and amino groups (Harper & Tappel, 1957), sulphur dioxide protects the vitamin C but has only a limited effect on the development of the brown colour (Draudt & Huang, 1966).…”
Section: Maillard Reactionmentioning
confidence: 99%
“…Pemberian sulfur dioksida pada penanganan buah dinilai dapat menurunkan oksidasi asam askorbat pada buah. Selain itu, juga dapat mencegah pencoklatan pada buah [25].…”
Section: Perubahan Karakteristik Fisikunclassified